2014
DOI: 10.1155/2014/839585
|View full text |Cite
|
Sign up to set email alerts
|

IVS1 −397T>C Estrogen ReceptorαPolymorphism Is Associated with Low-Grade Systemic Inflammatory Response in Type 1 Diabetic Girls

Abstract: Purpose. The study aimed to investigate the influence of estrogen receptor α (ER-α) genotypes on inflammatory response and development of microvascular complications in girls with type 1 diabetes. Methods. 152 young regularly menstruating girls with diagnosed type 1 diabetes and 84 young, healthy menstruating girls were recruited. ER-α genotyping was carried out by PCR. Serum concentrations of 17β-estradiol, as well as IL-6, TNF-α, VEGF, and IL-10, were measured. CD4+Foxp3+ TH17 cells were isolated and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Similarly to our previous paper, regarding IVS1 −397TNC polymorphism (Ryba et al, 2011;Ryba-Stanisławowska et al, 2014), we found that T allele is associated with enhanced inflammatory response in DM1 boys. Our study revealed that boys possessing CC genotype had lower IL-6 and CRP serum level than their counterparts with CT and TT genotype.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly to our previous paper, regarding IVS1 −397TNC polymorphism (Ryba et al, 2011;Ryba-Stanisławowska et al, 2014), we found that T allele is associated with enhanced inflammatory response in DM1 boys. Our study revealed that boys possessing CC genotype had lower IL-6 and CRP serum level than their counterparts with CT and TT genotype.…”
Section: Discussionsupporting
confidence: 90%
“…In another study conducted on DM1 adolescent girls, we have discovered that individuals carrying CC genotype were characterized by greater level of CD4+ Foxp3+ Tregs and simultaneous lowest TNF serum level in comparison to patients with CT and TT genotypes (Ryba et al, 2011). Moreover, elevated levels of analyzed proinflammatory factors (Th17 cells, cytokines) in DM1 girls carrying TT genotype promoted enhanced inflammatory response, which may cause diabetic-related microvascular complications (Ryba-Stanisławowska et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Similarly to previous reports regarding PvuII ER - α gene polymorphism in a smaller group of girls [ 19 , 20 ] and boys [ 21 ] with DM1, researchers have found that CC genotype is associated with weakened inflammatory response. CC genotype bearing girls produced more 17β-estradiol and had lower CRP, IL-6, and TNF-α serum level than their counterparts with CT and TT genotype.…”
Section: Discussionsupporting
confidence: 69%
“…In our previous study [ 19 ], we have shown that diabetic girls carrying CC genotype were characterized by greater population of CD4 + Foxp3 + Tregs and simultaneous lower TNF serum level in comparison to girls carrying CT or TT genotype. Moreover, elevated levels of analyzed proinflammatory factors (Th17 cells, cytokines) in DM1 girls carrying TT genotype promoted enhanced inflammatory response, which led to development and progression of diabetic microvascular complications [ 20 ]. In another study conducted on DM1 boys, researchers have discovered that individuals carrying CC genotype had lower blood pressure, IL-6, and CRP serum levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a gene involved in androgen synthesis was associated with RA (Stark et al 2015), and we show that androgen-responsive genes across the genome are enriched for association signal and sex differences. Although estrogen biology has been associated with comorbidities of T1D (Ryba et al 2011;Ryba-Stanisławowska et al 2014;Słomiński et al 2015), our results are the first to suggest a global impact on risk. Interestingly, we observed several examples of an increased proportion of heritability in AR genes in females, and for ER genes in males.…”
Section: Discussionmentioning
confidence: 62%